“Why would I bother?” Understanding prosumer motivations and engagement in renewable energy communities: a qualitative study of polish photovoltaic installation owners - Bielecki, Maksymilian; Neska, Ewa; Kowalska-Pyzalska, Anna (Frontiers in Energy Research, 2025)
Renewable Energy Communities (RECs) play a vital role in promoting decentralized, sustainable energy systems by enabling local stakeholders to collectively generate, share, and manage renewable energy resources. This enhances community resilience and environmental stewardship. The development and efficient functioning of RECs depend not only on technical or economic factors but also on numerous socio-psychological variables deeply rooted in local historical, political, economic, and cultural contexts. Our study aimed to understand the motivations and barriers to participation in RECs through thematic analysis of qualitative data obtained from in-depth interviews with current and prospective prosumers in Poland. The study’s findings are twofold. First, they offer a deeper understanding of the mechanisms shaping perceptions of RECs and the factors contributing to the success of future implementations and policies, structured according to Bronfenbrenner’s socio-ecological model. Second, the findings have broader methodological implications, highlighting the necessity of accounting for socio-cultural heterogeneity, embedding research practices in the local context, and promoting interdisciplinarity as the foundation for effectively shaping future policies.